2012
DOI: 10.1108/02630801211288215
|View full text |Cite
|
Sign up to set email alerts
|

Insights of architects’ knowledge of the Code for Sustainable Homes (CSH) in relation to low carbon housing design and delivery in the UK

Abstract: Purpose -The purpose of the paper is to report research conducted to explore the insights of UK architects on the Code for Sustainable Homes (CSH) in relation to low carbon housing design and delivery. Design/methodology/approach -To explore the awareness and knowledge of CSH in low carbon housing design and delivery in the UK, a mixed method approach comprising of interviews with architects in practice and academia were combined with questionnaires to UK sustainable architectural practices. Findings -The resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…A survey by Baba et al found that a significant proportion of architects do not consider the Code to be an effective way of providing high quality homes and offering design solutions. 58.8 percent rated the CSH as "effective," 5.9 percent "very effective," 32.4 percent ineffective and 2.9 percent very ineffective for achieving high quality new homes in the UK compared to 50 percent effective, 41.2 percent ineffective and 8.8 percent very ineffective in providing design solutions (Baba et al, 2012). Prior studies cited above also refer to the technology focus of the Code e.g.…”
Section: Discussionmentioning
confidence: 99%
“…A survey by Baba et al found that a significant proportion of architects do not consider the Code to be an effective way of providing high quality homes and offering design solutions. 58.8 percent rated the CSH as "effective," 5.9 percent "very effective," 32.4 percent ineffective and 2.9 percent very ineffective for achieving high quality new homes in the UK compared to 50 percent effective, 41.2 percent ineffective and 8.8 percent very ineffective in providing design solutions (Baba et al, 2012). Prior studies cited above also refer to the technology focus of the Code e.g.…”
Section: Discussionmentioning
confidence: 99%